PENGARUH SELF-ESTEEM TERHADAP SELF-PRESENTATION DI MEDIA SOSIAL PADA GENERASI Z - Eka Risti Gloria Gulo; Freddy Butarbutar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of self-esteem on self-presentation among Generation Z on social media, focusing on the dimensions of real self-presentation, ideal self-presentation, and false self-presentation. This research employed a quantitative explanatory approach involving 350 Generation Z respondents in Medan City selected through purposive sampling. Data were collected using an online questionnaire consisting of the Rosenberg Self-Esteem Scale (RSES) and the Self-Presentation on Facebook Questionnaire (SPFBQ), which was adapted to the context of social media use in Indonesia. Data were analyzed using simple linear regression with IBM SPSS Statistics version 20. The findings indicate that self-esteem has a positive and significant effect on real self-presentation and a negative and significant effect on false self-presentation. However, self-esteem does not significantly influence ideal self-presentation. The results suggest that individuals with higher self-esteem tend to present themselves more authentically and are less likely to display false identities on social media. Meanwhile, ideal self-presentation appears to be influenced by factors beyond self-esteem, such as social validation and digital culture.